Ultrasound-guided percutaneous transluminal angioplasty through arteriovenous fistular access(1):equipment selection for and establishment of the access - 詹申; 张丽红; 王玉柱 (Linchuang shenzangbing zazhi)
Ultrasound-guided percutaneous transluminal angioplasty(PTA)for arteriovenous access stenosis/occlusion has developed rapidly in China in recent years,but as a relatively emerging technology,many vascular access doctors have no sufficient master of their technique details,and the equipment applications are poorly standardized.The author aims to conduct a series of discussions on this technology.As the first step of endovascular therapy,an appropriate approach can make the PTA process more effective.This article will popularize the characteristics and selection of equipment required for the access establishment for ultrasound-guided PTA.In addition,the access establishment should follow the principle of easy puncture;convenient operation,facilitation in the passage of stenotic lesions;easy hemostasis after completion of treatment.The access can be established in outflow vein,brachial artery,the distal radial artery,arteriovenous graft and so on.The access site and direction should be based on the comprehensive consideration of the lesion location and nature.